Peran Pemerintah dalam Pelaksanaan Vaksin Covid-19 di Kelurahan Kadolo Kecamatan Kokalukuna Kota Baubau - Nasir Lamadika; Nastia Nasria; Muh Askal Basir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The purpose of this study is the Government's Role in the Implementation of the Covid-19 Vaccine in Kadolo Village, Kokalukuna District, Baubau City. The type of research used in this research is descriptive research with a qualitative approach. Data collection techniques are Observation, Interview, Documentation and Literature Study. Data analysis techniques in research are data reduction, data presentation, and drawing conclusions. The results obtained in the study are the function of the government as a motivator and encouragement to the local community, where the implementation of government vaccinations must be able to encourage the community so that people want to carry out vaccines; The government as a stabilizer, in implementing government vaccinations, must be able to ward off bad issues about vaccines, for that the government conveys positive news and information regarding the benefits of this COVID-19 vaccine to the public. So it is hoped that the community will not be anxious and have the desire to receive the vaccine voluntarily without any coercion. The government as a dynamist is that in implementing the Covid-19 vaccine, it must move multi-stakeholder participation when stagnation occurs in the development process and there are many doubts from the public about the vaccine.